KONSEP SIDRAT AL-MUNTAHÃ DALAM AL-QUR’AN (Studi Penafsiran ?an?âwî Jauharî al-Misrî, Ahmad Mus?ofâ Al-Marâghî dan Sa'îd Hawwâ) - Sayyidah Fatimatuz Zahro; Ghozi Mubarok (Institut Dirosat Islamiyah Al-Amien Prenduan, 2024)
Textual and contextual interpretation needs to be done, seeing the number of words in the Qur'an that need to be explained so as not to cause ambiguity (more than one meaning) one of which is about Sidrat Al- Muntaha which is believed by some Muslims to be the last place of togetherness of the Prophet Muhammad SAW with the Jibril AS in the Mi'raj event. According to modern and classical mufasir, Sidrat Al-Muntaha has slight differences in interpreting or defining it both linguistically and in terms, location, form and function. In this study, we will discuss the interpretation of the three modern mufasir, namely Tantawi Jauhari Al-Misri, Ahmad Mustafa Al-Maraghi and Sa'id Hawwa in explaining how the concept of Sidrat Al-Muntaha as well as the differences and similarities of the three mufasir about Sidrat Al-Muntaha. The research method used is library research, then the focus of the discussion uses me. After conducting research, it can be concluded that the interpretation of the three mufasir about the concept of Sidrat Al-Muntaha has two categories including: First, about the source of interpretation used by all mufasir that prioritizes atsar over ra'yu. Second about the details of interpretation. The similarity of interpretation of the three mufasir above can be seen in terms of the presentation of interpretations, both taking the opinions of the mufasir, in explaining the concept of Sidrat Al-Muntaha they both connect it with the events of Mi'raj, the three mufasir do not give ijtihad in interpreting about Sidrat Al-Muntaha. Meanwhile, the difference is that when the three mufasir explain the concept of Sidrat Al-Muntaha both in terms of definitions in language and terms, in interpreting the meaning of the words Sidrah and Al-Muntaha, their location, form and function, the systematics of writing, when interpreting verses about the events of Mi'raj, the sources of passages from hadith and the mufasir, the difference in explaining the concept of Sidrat Al-Muntaha with certain scientific debates.